Documents related to John Maynard Keynes, Institutionalism at Chicago & Frank H. Knight (Research in the history of economic thought and methodology, 2013)
The original 1933 "National self-sufficiency" lecture by John Maynard Keynes : its political economic context and purpose / Mark C. Nolan -- National self-sufficiency / John Maynard Keynes -- Studying institutional economics at Chicago in the 1930s : the case of Arthur Bloomfield / Pier Francesco Asso, Luca Fiorito -- Thorstein Veblen and his analysis of business enterprise / Arthur I. Bloomfield -- Frank H. Knight on institutionalism and economics / Ross B. Emmett -- Institutional history and the classical economics / Frank H. Knight -- "It is a long time between drinks" : the friendship of Frank H. Knight and Frederick D. Kershner / Ross B. Emmett -- The correspondence between Frank H. Knight and Frederick D. Kershner, 1915-1951 / Ross B. Emmett